2021
DOI: 10.3390/ijms22031117
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Nodule Number in Legumes Is a Balance of Three Signal Transduction Pathways

Abstract: Nitrogen is a major determinant of plant growth and productivity and the ability of legumes to form a symbiotic relationship with nitrogen-fixing rhizobia bacteria allows legumes to exploit nitrogen-poor niches in the biosphere. But hosting nitrogen-fixing bacteria comes with a metabolic cost, and the process requires regulation. The symbiosis is regulated through three signal transduction pathways: in response to available nitrogen, at the initiation of contact between the organisms, and during the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 93 publications
1
40
0
Order By: Relevance
“…This suggests that ethylene is not the only factor involved in the inhibition of nodulation by nitrate. Indeed, it has been shown that the autoregulation of nodulation (AON) pathway also contributes to the inhibition of nodulation by exogenous nitrate [ 23 , 56 , 57 , 58 ]. Genetic studies on L. japonicus revealed a role of HAR1 in controlling sensitivity to exogenous sources of fixed forms of nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ethylene is not the only factor involved in the inhibition of nodulation by nitrate. Indeed, it has been shown that the autoregulation of nodulation (AON) pathway also contributes to the inhibition of nodulation by exogenous nitrate [ 23 , 56 , 57 , 58 ]. Genetic studies on L. japonicus revealed a role of HAR1 in controlling sensitivity to exogenous sources of fixed forms of nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chaulagain and Frugoli [41], legumes balance the number of nodules formed with the plant's need for N by integration of the outputs of least three signalling pathways. These include a pathway for nodule initiation, an inhibitory pathway for nodule number, and an inhibitory pathway based on N sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A suggested mode of control involves auxin transport from the shoot to the root to regulate nodule numbers as seen from the differential expressions of auxin inducible proteins in mutant and wild type M. truncatula [ 89 , 90 ]. The second possibility is the regulation of the plant defense mechanisms that may arrest or inhibit nodulation [ 91 ].…”
Section: The Two-phase Microbial Communitiesmentioning
confidence: 99%